Bank Specific and Macroeconomics Dynamic Determinants of Credit Risk in Islamic Banks and Conventional Banks - Waemustafa, Waeibrorheem; Sukri, Suriani (International Journal of Economics and Financial Issues, 2015)
The study analyzes the macroeconomic and bank specific determinants of credit risk in Islamic and Conventional Banks. Multivariate Regression analysis is applied on the sample of 15 conventional banks and 13 Islamic Banks in Malaysia over the period between 2000-2010. The finding shows that the banks specific determinants of credit risk are uniquely influenced the credit risk formation of Islamic and Conventional banks. The study found that risky sector financing; regulatory capital and Islamic Contract are significant to credit risk of Islamic banks. For Conventional Banks, loan loss provision, debt-to-total asset ratio, regulatory capital, size, earning management and Liquidity are significant factors influencing credit risk. As for macroeconomic factors only Inflation and M3 are significant to credit risk for both Islamic and Conventional banks. Keywords: Determinants of Credit Risks; Murabahah and Bai-Bhithaman Ajil; Islamic contracts; Islamic and Conventional Banks. JEL Classifications: E3; E5; E5; G2; P4